THU0061 Vitamin D Insufficiency and Deficiency in Two European Cohorts of Patients with Inflammatory Rheumatic Disorders. (10th June 2014) - Vacca, A.; Porru, G.; Dessole, G.; Mathieu, A.; Cormier, C.; Fulla, Y.; Kahan, A.; Allanore, Y.
Abstract : Background: Vitamin D plays an important role in the modulation of immune system and epidemiologic data indicate low vitamin D levels in autoimmune diseases such as rheumatoid arthritis (RA), connective tissue disorders, inflammatory bowel diseases and multiple sclerosis. Several studies reported contradictory results regarding correlation between disease activity and vitamin D levels in these diseases. Objectives: To assess 25-OH vitamin D concentrations in 2 independent cohorts of patients affected by inflammatory rheumatic disorders (IRD) and correlations with disease activity and disability. Methods: We retrospectively analyzed 420 patients (246 RA, 100 ankylosing spondylitis (SA), 74 psoriatic arthritis (PsA) followed at Rheumatology tertiary centers in Northern France (Paris) and Southern Italy (Cagliari). All patients underwent clinical and laboratory evaluation including serum calcium and phosphorus levels, 25-OH vitamin D and parathyroid hormone (PTH). Vitamin D concentrations <30 ng/ml were considered insufficiency, while values <10 ng/ml were classified as deficiency. Disease activity was assessed by DAS 28 in RA and PsA patients, and by BASDAI and BASFI in AS patients. Results: Vitamin D insufficiency and deficiency was very high: respectively 66% and 19% in RA, 76% and 10% in AS, 83% and11% in PsA. Their incidence was comparable between the two populations in RA (68% and 20% versus 62% and 18%, P = ns, respectively in the French and Italian patients), while it was significantly higher among French compared to Italian patients in AS and PsA (86% and 23% versus 61% and 0, P=0.005 and P=0.002; 89% and 20% versus 55% and 3%, P=0.002 and P=0.02, respectively in AS and PsA). Vitamin D supplementation was statistically different only in RA patients (53% versus 34%, P=0.003, respectively in French and Italian patients). In the combined populations, in RA patients, no correlation was observed between vit D and DAS score but treated patients with anti-TNF alpha agents had higher vitamin D levels (P=0.01). In SA patients low vitamin D concentrations correlated with higher BASFI (R = -0, 02; P<0.05). We did not find any correlation between vitamin D levels and the other evaluated parameters. Conclusions: A high incidence of vitamin D deficiency was found in IRD in the two populations, independently of geographic origin for RA, while a higher incidence was seen in French AS and PsA patients, suggesting a potential different influence of vitamin D on these diseases. By contrast, no correlations with disease activity were found except for disability index BASFI in AS patients. In our study, TNF alpha agents seem to improve vitamin D levels as well as disease activity, but it remains controversial if this is an effect linked to disease activity modulation or it directly depends from immunomodulatory properties of vitamin D. This finding encourage to perform randomized controlled studies for confirming that vitamin D supplementation could reduce the risk of autoimmunity or that it eases disease activity, although there is still not a clear consensus about the optimal circulating 25-OH vitamin D levels and the supplementation dosage for maintaining immune homeostasis. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5038